Local people's participation in community forest management : a case study of Con Cuong District, Nghe An, Vietnam - Nguyen Thi Huyen; Cochard, Roland; Thapa, Gopal B.; Shrestha, Rajendra Prasad; The Ford Foundation (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Similar to the situation of many developing countries, forest resources of Vietnam have been degrading lately both quantitatively and qualitatively. To combat forest degradation, community forest management has been developing in the uplands of Vietnam for a long time by ethnic minority groups and actively local people{u2019}s participation make a unique contribution to conserve and develop forest resources as well as protect environment. However, local people{u2019}s participation have some problems in nation forest allocation program, top-down approach and local people have unequal oppotinities to design, plan, implement, make decision and share benefits. Thus, the overall objectives of this study are to examine levels of local people{u2019} participation in community forest management activities and imply the ways to promote local people{u2019}s participation in community forest management in two villages located in Con Cuong district, Nghe An, Vietnam. This research conducted in two villages in Con Cuong district with a total number of 87 households samples for primary data collection. Many findings of the research reveal that local people involved in community forest management program in formalistic way and had low level of participation. Economic incentives, traditional and community characteristics and forced by local leaders have active encouragement in local people{u2019}s participation in community forest management. Unclear sharing mechanism, lack of supports and problem of laws act as obstacles to discourage local people{u2019}s participation in community forest management activities. Forest protection unit and local government consider as the important institutions for the process of community forest management activities and they play as supporter to local people in these activities.
A final thesis submitted in partial fulfillment of the requirement for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2010
Keywords: Community forests -- Vietnam -- Nghe An -- Management; Community forests -- Vietnam -- Nghe An -- Citizen participation